Association Between Mutation Size and Cardiac Involvement in Myotonic Dystrophy Type 1: An Analysis of the DM1-Heart Registry. (June 2017) - Chong-Nguyen, Caroline; Wahbi, Karim; Algalarrondo, Vincent; Bécane, Henri Marc; Radvanyi-Hoffman, Hélène; Arnaud, Pauline; Furling, Denis; Lazarus, Arnaud; Bassez, Guillaume; Béhin, Anthony; Fayssoil, Abdallah; Laforêt, Pascal; et al.
Abstract : Background—: In myotonic dystrophy type 1, the association between mutation size (CTG expansion) and the severity of cardiac involvement is controversial. Methods and Results—: We selected 855 patients with myotonic dystrophy type 1 (women, 51%; median age, 37 years), with genetic testing performed at the moment of their initial cardiac evaluation, out of 1014 patients included in the Myotonic Dystrophy Type 1-Heart Registry between January 2000 and December 2015. We studied the association between CTG expansion size and other baseline characteristics and (1) cardiac involvement at baseline and (2) the incidence of death, sudden death, and other cardiac adverse events. At initial presentation, the median CTG expansion size was 530 (interquartile range, 300–830). In multivariate analysis, larger expansions were associated with the presence at baseline of conduction defects on the ECG and left ventricular systolic dysfunction. In a median 11.5 years of follow-up period, 210 patients died (25%), including 32 suddenly (4%). Supraventricular arrhythmias developed over lifetime in 166 patients (19%), sustained ventricular tachyarrhythmias in 17 (2%), and permanent pacemakers were implanted in 181 (21%). In Cox regression analyses, larger CTG expansions were significantly associated with (1) total death, sudden death, and pacemaker implantation in a model, including CTG expansion size, age, sex, diabetes mellitus, and (2) all end points except sudden death in a model including all baseline characteristics. Conclusions—: The size of the CTG expansion in the blood of myotonic dystrophy type 1 patients is associated with total and sudden deaths, conduction defects, left ventricular dysfunction, and supraventricular arrhythmias. Clinical Trial Registration—: URL:https://www.clinicaltrials.gov . Unique Identifier: NCT01136330 Abstract : Supplemental Digital Content is available in the text.